Pendampingan dan Fasilitasi dalam Mempersiapkan Pertemuan Tatap Muka Terbatas Sesuai Protokol Kesehatan di SDN 001 Sungai Kunjang Kota Samarinda - Annisa Nurrachmawati; Lies Permana; Rina Tri Agustini (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
Online learning has the potential to affect a students’ academic achievement. Therefore, schools are encouraged to hold limited face-to-face meetings as COVID-19 cases begin to decrease. All schools should immediately begin preparing the requirements for getting permission to use limited face-to-face meetings. SDN 001 Sungai Kunjang Samarinda is one of them, and it is still having problems fulfilling these requirements. The activity's goal is to facilitated SDN 001 ready to meet the requirements of limited face-to-face meetings. Method of this community service implementation were consists of five stages, namely stage 1 licensing and policy identification, stage 2 awareness of problems, stage 3 the implementation of assistance and facilitation of limited face-to-face meetings preparation, stage 4 socialization of rules and Standard Operating Procedure (SOP) of limited face-to-face meetings implementation, and stage 5 the evaluation stage of activities. The results of this series of activities show that through the assistance of the school is able to arrange the rules and flow chart of limited face-to-face meetings implementation. After socializing to all teachers and education personnels, they understand the guidance of the implementation of limited face-to-face meetings in the education unit of the Joint Decree (SKB) 4 ministry. All teachers feel confident that they can be disciplined in carrying out health protocols in school after socialization. Furthermore, to strengthen the readiness of schools to implement limited face-to-face meetings, it is expected that this socialization will also be carried out to students and their parents.